Human health impacts related to water, sanitation and climate change - Medlicott, K.; France, J. de; Villalobos-Prats, E.; Gordon, B.; Graczyk, H.; Zandaryaa, S.; Mateo-Sagasta, Javier; Hada, R.; Caucci, S.; Smakhtin, Vladimir U.; Pories, L. (2020)
This chapter focuses on the human health impacts associated with changes in water quality and quantity due to climate change. Trends in morbidity and mortality are examined in the context of health risks associated with climate change, and response options related to water supply and sanitation are presented.